The theory and practice of military disengagement: Nigeria 1975-1979 - Pacheco, Orlando Enrique Perez (My University, 1991)
The purpose of this thesis is to study the theory and practice of military disengagertent with special emphasis on Nigeria's successful program from 1975 to 1979. The thesis examines the specific nature, scope and structure of the transference of federal authority from the military to civilian leadership in 1979. This transfer program represents, in its conception, execution and completion, the most comprehensive schedule of military disengagement to have emerged from post-independence and coup-riddled Africa. (Abbreviation abstract)
A thesis submitted to the faculty of Arts, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy
Keywords: NIGERIA--MILITARY GOVERNMENT--HISTORY.; NIGERIA--POLITICS AND GOVERNMENT--1975-1979.; NIGERIA--ARMY--HISTORY.; CIVIL-MILITARY RELATIONS--NIGERIA.